Development of Blended Learning Activities Based on 3CM (Cool-Critical-Creative-Meaningful) to Support Creativity and Good Character Students - Wahyudi, Wahyudi; Kusuma, Dani; Prihatnani, Erlina; Nova Hasti Yunianta, Tri; Amin, Nor Fadila (Journal of Nonformal Education, 2023)
Good character and creativity are two of the ten determining factors of a person's success. These two things are important to form in educational activities, especially in elementary schools. During the Covid-19 pandemic, this became a tough challenge to achieve. The new normal period is beginning, and a good and effective learning preparation is needed. The purpose of this study is to develop blended learning activities with the 3CM model to increase students' creativity and good character. Blended learning is one of the alternative learning modes that can be done. It requires appropriate design and learning activities. Blended learning that gives students the opportunity to develop critical, creative, meaning-ful thinking skills in a fun and challenging way. One of them is a blended learning design based on 3CM (Cool-Critical-Creative-Meaningful). Learning activities with blended learning can be done with full online or a combination of face-to-face and online. This research is RnD re-search with ASSURE design in 6 stages of development activity. The results of the development of blended learning activities based on 3CM learning are carried out in 4 activities, namely 1) it's time to play and challenge (cool), 2) it's time to criticize (critical), 3) it's time to be creative, 4) it's time to reflect and take meaning (meaningful). The results of the assessment of blended learning activities aspects of ease of access to learning score 4.48 (excellent), aspects of content, media and teaching materials score 4.57 (excellent) from the assessment of 45 teachers. Student response to aspects of ease of access to learning score 4.72 (excellent), aspects of content, media and teaching materials score 4.72 (excellent). The results of this study are proven to increase students' creativity and good character.